The reality of the application of the management of the system of learning Cassera in the schools Talaea Alghad for middle school in Tabuk city - Alasmari, Dorar Saleh; Alatawi, Hanan Afnan; Alasmari, Saleh Saad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the reality of the application of the management of the system of learning Cassera in the schools Talaea Alghad for middle school in Tabuk city , and also aimed to reveal the obstacles facing the application of the management of the system of learning Classera in the schools Talaea Alghad for middle school in Tabuk city , as well as aimed to reveal whether There are statistically significant differences between the average responses of members of the study community about the reality of applying the management of the Classera learning system in the schools Talaea Alghad middle school in Tabuk city due to the variables of experience in the schools Talaea Alghad vanguard, training courses in the use of Learning techniques, also aimed at detecting whether there are statistically significant differences between the averages of the response of the members of the study community about the obstacles facing the application of the management of the system of learning Classera in the schools Talaea Alghad middle school in Tabuk city due to the variables of experience in Tomorrow’s vanguard schools, training courses in the use of learning techniques, the study was based on the descriptive survey method, and the questionnaire was used as a data collection tool, and the study community is of (45) teachers, the whole community has been taken and the tool has been distributed to all of them, and recovered from it. (45) To make up 100 % of the study community. From the study community, the results of the study concluded that the reality of the application of the system of e-learning management Classera in the the schools Talaea Alghad middle school in Tabuk came with a high degree of approval, and also found that the obstacles facing the application of the electronic learning management system Classera in the schools Talaea Alghad For the middle stage in Tabuk city came with a low degree of approval, and also found statistically significant differences at the level of (α = 0.01) between the average responses of members of the study community according to the change of experience in the schools Talaea Alghad in favor of experienced teachers (more than 5 years), and also found statistically significant differences at the level of (α = 0.01) between the average responses of members of the study community towards the reality of applying the management of the Classera learning system in the schools Talaea Alghad middle school in Tabuk city depending on the variable courses in the use of learning techniques for the benefit of the teachers Who have more than two courses, and also found statistically significant differences at the level (α = 0.01) between the average responses of members of the study community towards the obstacles to the application of the management of the system of learning Classera in the schools Talaea Alghad middle school in Tabuk city depending on the variable experience in schools Talaea Alghad vanguard for female teachers with less than two years of experience, and also found statistically significant differences at the level of (α = 0.01) between the average responses of members of the study community towards the obstacles facing the application of the management of the system of learning Classera in the schools Talaea Alghad middle school in Tabuk Depending on the course variable for female teachers, they do not have training courses in the use of learning techniques.